Length in listening texts as a single determiner of difficulty for comprehension - Ilhan, Berk (My University, 2018)
Text length is considered as one of the factors that cause listening task difficulty along with others such as speechrate, clarity of voice, accents, text genre and topic. Despite all these factors, teachers sometimes consider textlength as the single reason for a listening activity’s difficulty. Not many studies have focused on the length as asingle determiner or whether there are other factors that are associated with text length or not. In order to contributeto the field, the present study has aimed to investigate whether text length is a single determiner for difficulty andif not what other difficulties students have when they listen to long texts. Both quantitative and qualitative datahave been collected. Reflection reports on the difficulties of the task constitute qualitative data whereas scores oncomprehension questions comprise quantitative data. Two long listening tasks were implemented with anexperimental group by dividing the length into manageable phases; meanwhile, with control group, they were doneall at once. Scores of the two groups in comprehension questions have been compared by using T-test analysis.The findings have indicated that text length cannot be a determining factor alone. In the experiment, the scores ofexperimental and control groups do not have a statistically significant difference. According to student reflectionreports, students have difficulties in listening long texts due to a lack of listening strategies, speech rate andpronunciation. Thus, text length might be better considered along with these factors.
Keywords: Eğitim; Eğitim Araştırmaları; Dil ve Dil Bilim